2017
DOI: 10.1111/vde.12453
|View full text |Cite
|
Sign up to set email alerts
|

Afoxolaner and fluralaner treatment do not impact on cutaneous Demodex populations of healthy dogs

Abstract: Treatment with afoxolaner or fluralaner does not impact on cutaneous Demodex populations of normal dogs over a 90 day period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…However, results of the present and previous [1] studies show that either administration approach (topical or oral) provides drug levels sufficient to achieve mite elimination. At the same time, it is interesting that an investigation into mite levels on healthy dogs treated with fluralaner did not find a significant effect on mite populations at the end of the study period [7]. One possible explanation could be that there is a difference in drug levels achieved in hair follicles in dogs with generalised demodicosis compared to the hair follicles of the unaffected dog.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results of the present and previous [1] studies show that either administration approach (topical or oral) provides drug levels sufficient to achieve mite elimination. At the same time, it is interesting that an investigation into mite levels on healthy dogs treated with fluralaner did not find a significant effect on mite populations at the end of the study period [7]. One possible explanation could be that there is a difference in drug levels achieved in hair follicles in dogs with generalised demodicosis compared to the hair follicles of the unaffected dog.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation could be that there is a difference in drug levels achieved in hair follicles in dogs with generalised demodicosis compared to the hair follicles of the unaffected dog. However, the above must be considered with caution, as the referenced study [7] evaluated the presence of mite DNA in clinically healthy animals, and not from skin scrapings of visually affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…populations of normal dogs over a 90 day period and thus does not eliminate the mite population on a dog. However, this study was based on a DNA detection using simple PCR with no quantification methods or evaluation of the viability of the mites [ 28 ]. Those results should therefore be considered as not conclusive and additional studies are necessary to better understand the effect of isoxazoline on Demodex mite populations.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant decreases in mites and lesions occurred during the first 7 days [ 88 ]. In a study of healthy dogs with populations of Demodex mites, cutaneous populations of Demodex over the 90-day period were not affected by a treatment of fluralaner or afoxolaner [ 89 ]. It was suggested that isoxazoline treatments may not completely eliminate Demodex mites, but only return them to a more natural population level.…”
Section: Chemical Treatmentsmentioning
confidence: 99%